A clinical study on acupuncture in combination with routine rehabilitation therapy for early pain recovery of post-stroke shoulder-hand syndrome - Zheng, Jinling (Exp Ther Med, 2018)
The clinical effect of acupuncture in combination with rehabilitation therapy for post-stroke shoulder-hand syndrome (SHS) was explored. Patients (178) with post-stroke SHS who received treatment in the Dalian Second Hospital from March 2012 to March 2016 were included in this study. The patients were divided into experimental group (89 cases) and control group (89 cases). Patients in the control group received rehabilitation therapy, while those in the treatment group received acupuncture treatment in addition to rehabilitation therapy. Visual analogue scale (VAS) was applied to assess the pain degree of patients. Fugl-Meyer assessment (FMA), functional comprehensive assessment (FCA) and assessment of quality of life (QoL) were used to evaluate rehabilitation condition of the patients. Early pain relief, rehabilitation of upper extremity motor function and improvement of QoL after treatment were compared between the two groups. The scores of VAS, FMA, FCA and QoL showed obvious differences between the two groups after treatment (P<0.05). The scores of the experimental group were significantly better than those of the control group, and the improvement in upper extremity motor function of the patients in the experimental group was better than that of the patients in the control group. The total effective rate of the patients in the experimental group was higher than that of control group (P<0.05). The effect in improving the upper extremity motor function of the patients in the experimental group was better than that of control group. The scores of QoL of the patients in the experimental group were better than that of the patients in the control group (P<0.05). In conclusion, acupuncture in combination with rehabilitation therapy can improve early pain and rehabilitation significantly and enhance QoL for patients with post-stroke SHS, which is worthy of being widely used in clinical practice.